((n+1)(n+2)(2n+3))/6

Simple and best practice solution for ((n+1)(n+2)(2n+3))/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((n+1)(n+2)(2n+3))/6 equation:


n in (-oo:+oo)

((n+1)*(n+2)*(2*n+3))/6 = 0

( 2*n+3 )

2*n+3 = 0 // - 3

2*n = -3 // : 2

n = -3/2

( n+1 )

n+1 = 0 // - 1

n = -1

( n+2 )

n+2 = 0 // - 2

n = -2

n in { -3/2, -1, -2 }

See similar equations:

| x=144p/y | | -10(n+10)=-270 | | 3x+16=180 | | 216-2x=180 | | 4x^2-29x-12=0 | | y+75+3y+5=180 | | 8x-5+3=x-7+10 | | w/12=64 | | 3x+7+5x-35=180 | | 6x+6x=16x-42 | | 12/64 | | (6n+9n^6+13n^5)-(-16n^5+2n^6-5n)= | | 6z-7q=2z+8 | | 2e^5x+3=5 | | 2/9a=2/3 | | 6n+9n^6+13n^5= | | 1/3x+1/4y=12 | | x^3-2x^2-7x+14=0 | | 12y+30=24(3.25)+18 | | k^2-16+225=0 | | 3.7=6.1-0.4x | | -1/5x-3=17 | | 8/4-8=12 | | A+B+B+B+80+90= | | -4.1+-7z=3.6 | | 12-3(2w+1)=7w-3(7w+w) | | 2(x-1)=4x-4 | | 2x+2x-9=11 | | 4=5C-(-14) | | 5t-1=60-5 | | 1/2(-3)+5 | | -7/6x+5/4x=2 |

Equations solver categories